Post-Traumatic Growth and Resilience among University Students in Baghdad: A Conceptual Study - Haider Kamil Mahdi; Shahabudin Bin Hashim (Institute of Advanced Engineering and Science, 2013)
Posttraumatic Growth (PTG) refers to positive changes in human life elicited by exposures to traumatic events, such as war and terror. The fact that Iraqi university students continue their studies not long after a bomb explosion or deaths of significant others related to the War in 2003 indicated that they possess certain degree of resilience. This study conceptualized the causal relationship between the resilience and the level of PTG among Iraqi university students after being exposed to traumatic events in the form of the War in 2003. Thorough discussion on the previous studies have been done, recommendations on the sampling methods, as well as the instruments, were made. Significance of the empirical research related to this conceptualized relationship is discussed at the end of this paper.DOI: http://dx.doi.org/10.11591/ijere.v2i4.3872